Conformational switches and redox properties of the colon cancer‐associated human lectin ZG16. (15th June 2021) - Javitt, Gabriel; Kinzel, Alisa; Reznik, Nava; Fass, Deborah
Abstract : Zymogen granule membrane protein 16 (ZG16) is produced in organs that secrete large quantities of enzymes and other proteins into the digestive tract. ZG16 binds microbial pathogens, and lower ZG16 expression levels correlate with colorectal cancer, but the physiological function of the protein is poorly understood. One prominent attribute of ZG16 is its ability to bind glycans, but other aspects of the protein may also contribute to activity. An intriguing feature of ZG16 is a CXXC motif at the carboxy terminus. Here, we describe crystal structures and biochemical studies showing that the CXXC motif is on a flexible tail, where it contributes little to structure or stability but is available to engage in redox reactions. Specifically, we demonstrate that the ZG16 cysteine thiols can be oxidized to a disulfide by quiescin sulfhydryl oxidase 1, which is a sulfhydryl oxidase present together with ZG16 in the Golgi apparatus and in mucus, as well as by protein disulfide isomerase. ZG16 crystal structures also draw attention to a nonproline cis peptide bond that can isomerize within the protein and to the mobility of glycine‐rich loops in the glycan‐binding site. An understanding of the properties of the ZG16 CXXC motif and the discovery of internal conformational switches extend existing knowledge relating to the glycan‐binding activity of the protein. Abstract : Zymogen granule membrane protein 16 (ZG16) is an animal lectin present in the intestine. Here, we show that ZG16 has a redox‐active CXXC disulfide in a non‐canonical structural context: on a flexible, carboxy‐terminal tail. Additional conformational heterogeneity is seen in the glycan‐binding region of ZG16, including a rare cis‐trans isomerization of a peptide bond that does not precede a proline.